Cytisine-Pterocarpan Derived Compounds: Biomimetic Synthesis and Apoptosis-Inducing Activity in Human Breast Cancer Cells - Ting-Ting Peng; Xuan-Rong Sun; Ren-Hao Liu; Lu-Xia Hua; Dong-Ping Cheng; Bin Mao; Xing-Nuo Li (Molecules, 2018)
Cytisine-pterocarpan derived compounds were biomimetically synthesized with (-)-cytisine and (-)-maackiain via a N,N-4-dimethyl-4-aminopyridine (DMAP)-mediated synthetic strategy in a mild manner. In the present study, tonkinensine B (4) was elaborated in good and high yields with the optimized reaction conditions. The in vitro cytotoxicity of compound 4 was evaluated against breast cancer cell lines and showed that 4 had a better cytotoxicity against MDA-MB-231 cells (IC50 = 19.2 μM). Depending on the research on cytotoxicities of 4 against RAW 264.7 and BV2 cells, it was suggested that 4 produced low cytotoxic effects on the central nervous system. Further study indicated that 4 demonstrated cytotoxic activity against MDA-MB-231 cells and the cytotoxic activity was induced by apoptosis. The results implied that the apoptosis might be induced by mitochondrion-mediated apoptosis via regulating the ratio of Bax/Bcl-2 and promoting the release of cytochrome c from the mitochondrion to the cytoplasm in MDA-MB-231 cells.